Functions And Responsibilities Of The Regional Supervisory Council In Carrying Out Supervision And Guidance Of Notaries - Kintan Salma Waluya; Tetti Samosir; Fitra Deni (CV. AFDIFAL MAJU BERKAH, 2026)
Sanctions against notaries suspected of violating the code of ethics or violation of the exercise of office are carried out through tiered examination stages by the Supervisory Board in accordance with the organizational structure of notary supervision. The procedure starts from the regional Supervisory Council (MPD) which forms an examination team to trace reports or complaints against notaries. After the examination, the MPD prepares the minutes of the examination and provides recommendations for sanctions, which are then submitted to the regional Supervisory Council (MPW). MPW conducts a follow-up hearing and, if sufficient evidence is found, can impose light sanctions such as a written reprimand or moderate sanctions in the form of temporary dismissal for three months. The nature or type of research used in this study is normative research, which aims to examine the principles of legality, justice, and legal certainty using legislation, positive legal norms, and professional ethics, while the nature of the research used in this study is descriptive. Descriptive research is intended to describe data as accurately as possible about humans, conditions, or other phenomena. The functions and responsibilities of the regional Supervisory Council (MPW) in monitoring and coaching notaries have not been running optimally. In practice, MPW tends to focus only on repressive aspects in the form of sanctions without being balanced by coaching and education. MPW is also less ensure the fulfillment of the right of notaries to defend themselves, so the role of supervision does not provide a balanced protection between the public interest and the rights of the profession. Weaknesses in the coordination and implementation of supervisory procedures have an impact on the declining effectiveness of the notary supervision system at the regional level.